2012
DOI: 10.4049/jimmunol.1100769
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Infection-Induced Expansion of Effector T Cells Overcomes the Suppressive Effects of Regulatory T Cells via an IL-2 Deprivation Mechanism

Abstract: Regulatory Foxp3+ T cells are a critical cell population that suppresses T cell activation in response to microbial and viral pathogens. We identify a cell-intrinsic mechanism by which effector CD4+ T cells overcome the suppressive effects of Treg cells in the context of three distinct infections, Toxoplasma gondii, Listeria monocytogenes, and vaccinia virus. The acute responses to the parasitic, bacterial, and viral pathogens resulted in a transient reduction in frequency and absolute number of Treg cells. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 45 publications
6
77
1
Order By: Relevance
“…To explore the possible mechanisms by which the adjuvant-only group manifested better protection than did the vaccinated groups, we hypothesized that immune regulators such as Tregs and MDSCs are involved. Downregulation of negative regulators such as Tregs during acute infection has been shown to be essential for optimal T cell responses and host resistance to pathogens such as Toxoplasma gondii, Listeria monocytogenes, and vaccinia virus, and restoration of Tregs led to enhanced susceptibility to these pathogens (44). In this study, however, we found positive associations of set-point VLs only with MDSCs, but not with Tregs.…”
Section: Discussioncontrasting
confidence: 56%
“…To explore the possible mechanisms by which the adjuvant-only group manifested better protection than did the vaccinated groups, we hypothesized that immune regulators such as Tregs and MDSCs are involved. Downregulation of negative regulators such as Tregs during acute infection has been shown to be essential for optimal T cell responses and host resistance to pathogens such as Toxoplasma gondii, Listeria monocytogenes, and vaccinia virus, and restoration of Tregs led to enhanced susceptibility to these pathogens (44). In this study, however, we found positive associations of set-point VLs only with MDSCs, but not with Tregs.…”
Section: Discussioncontrasting
confidence: 56%
“…However, our data indicate that in Prf1 2/2 mice the level of CD8 1 T-cell immune activation crosses a critical threshold, at which point the CD8 1 T cells become capable of diverting the normally antiinflammatory IL-2 feedback loop into a proinflammatory circuit, driving the precipitous decrease in Treg cell numbers and feed-forward inflammation. Several synergistic events appear to participate in this process, with IL-2 production by CD4 1 T cells being suppressed 28 (an effect that might be mediated directly by IFN-g 29 ) and release of sCD25 by CD8 1 T cells and reversal of the CD25 expression hierarchy allowing preferential consumption of IL-2 by CD8 1 T cells at the expense of Treg cells. Critically, this inverted hierarchy meant that IL-2 supplementation, which is normally protective in patients with Treg cell deficiencies, drove excessive CD8 1 T-cell activation and led to the premature death of Prf1 2/2 mice.…”
Section: Discussionmentioning
confidence: 99%
“…IL-2/anti-IL-2 complexes were prepared as described in the literature (14,20) with minor modifications. Recombinant IL-2 and anti-IL-2 monoclonal antibody (MAb; clone JES6-1A12) were obtained from eBioscience.…”
Section: Methodsmentioning
confidence: 99%
“…They constitutively express the interleukin-2 (IL-2) receptor alpha chain (IL2R␣), a surface receptor also known as CD25, and the intracellular fork head box-p3 transcription factor (Foxp-3) marker (16). The role of Tregs after infection with type II strains has been fully described (14,(17)(18)(19)(20)(21), and Tregs have been clearly implicated in the mortality of C57BL/6 mice after oral infection in the lethal ileitis model (14). The collapse of Tregs is correlated with pathogenicity and occurs only under highly pathogenic conditions since oral infection of BALB/c mice with a type II strain did not induce a reduction in the levels of Tregs (14).…”
mentioning
confidence: 99%